Design, Beam-Wave Interaction, and Efficiency Enhancement Studies of Millimeter Wave Gyro-TWT with a Three-Stage Depressed Collector - Akash; Thottappan M. (My University, 2025)
In this article, a W -band gyrotron traveling wave tube (gyro-TWT) amplifier that uses periodically dielectric-loaded (PDL) waveguide and operates in TE01 mode is designed and studied for its stability against backward wave oscillations and beam wave interaction behavior. The subassemblies including a magnetron injection gun using E-GUN code, RF output window, and electron collector using 'MAGIC 3-D' are investigated. The present particle-in-cell (PIC) simulation of millimeter-wave gyro-TWT results in a peak RF power 195 kW in TE01 mode with an electronic efficiency of 28% and a saturated gain of 63 dB. Further, the overall efficiency of the device is enhanced by using a three-stage depressed collector, which is designed and simulated using 'MAGIC 3-D. ' The collection efficiency of the present collector is calculated as 74% and the overall efficiency of the gyro-TWT is improved to 60%. © 1973-2012 IEEE.